Evaluasi Pasca Pelatihan: Analisis Perubahan Sikap dan Perilaku Kepemimpinan Nasional Pada Pusdiklat Tenaga Administrasi - Kusriyah, Siti (Balai Diklat Keagamaan Surabaya, 2024)
National Leadership Training level II (PKN II) for high level pratama positions (echelon II) needs to be evaluated to determine the extent of changes in song behavior and the impact of the training. Through post-training evaluation, it is found to what extent the training objectives have been achieved. The research uses Kirkpatrick's third stage behavioral evaluation model (behavior). Supporting data was obtained from questionnaire instruments, interviews and documentation, then analysis was carried out using quantitative descriptive analysis techniques. questionnaires were distributed to trainees and the trainees' superiors (mentors). Evaluation at the third stage of behavior is categorized into three aspects, namely aspects of attitude, behavior, impact and sustainability of the change project. The results of the third level evaluation were distributed to alumni and mentor respondents, namely in the aspect of changing attitudes and behavior of alumni with an average value of 3.48. The impact of training on alumni stakeholders was 3.23. From the results of alumni and mentor respondents, it shows that the Level II National Leadership Training succeeded in achieving its goals well, obtaining scores for all aspects above 3.35 with good qualifications. The behavioral attitudes of strategic leaders in practicing energy management are able to manage strategies and utilize the resources they have, are able to manage organizational members to adapt to threats, obstacles and take advantage of the opportunities they have, and are able to influence external stakeholders, so that innovation and creativity can run effectively and sustainably . The resulting innovation can influence the development of government-private partnerships that support national development policies and encourage national competitiveness.